2022
DOI: 10.1155/2022/3057829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramic Nano Fillers in Jute Fibre Composites

Abstract: The demand and applications of bolstered plastics such as natural, attainable, biodegradable, and fibres were developing worldwide in industries beginning from home utilities to aerospace applications. The high cost and weight of synthetic fibres were bolstered by a multitude of concerns. Subsequently, it is far vital to create a natural fibre combination with a matrix to accumulate the most efficient common presentation. In this present study, a composite is made of a natural fibre (jute) reinforced with viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Epoxy resin is most extensively used as the matrix material for manufacture of fiber-reinforced polymer composites for wide structural and industrial applications because of its superior adhesion, better dimensional stability, and high chemical and heat resistance characteristics. Various engineering materials were constructed by using epoxy resin as the matrix material. , It has been found that the interface-to-volume ratio and the size of the filler have a significant impact on how the mechanical characteristics of composites can be improved by matrix modification. , Therefore, the alteration of the polymer matrix is being done by nanofillers. The alteration of the composite interface by a reinforcing mechanism has already been covered in certain research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxy resin is most extensively used as the matrix material for manufacture of fiber-reinforced polymer composites for wide structural and industrial applications because of its superior adhesion, better dimensional stability, and high chemical and heat resistance characteristics. Various engineering materials were constructed by using epoxy resin as the matrix material. , It has been found that the interface-to-volume ratio and the size of the filler have a significant impact on how the mechanical characteristics of composites can be improved by matrix modification. , Therefore, the alteration of the polymer matrix is being done by nanofillers. The alteration of the composite interface by a reinforcing mechanism has already been covered in certain research.…”
Section: Introductionmentioning
confidence: 99%
“…Various engineering materials were constructed by using epoxy resin as the matrix material. 3 , 4 It has been found that the interface-to-volume ratio and the size of the filler have a significant impact on how the mechanical characteristics of composites can be improved by matrix modification. 5 , 6 Therefore, the alteration of the polymer matrix is being done by nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond 8 wt.% of SiC, the mechanical properties were decreased due to more voids and agglomeration. Padma Rao et al 15 incorporated SiO 2 as ceramic filler in jute/vinyl ester composite to improve the mechanical properties such as tensile, flexural, compressive strength and hardness. According to results, the mechanical properties were improved when jute/vinyl ester composite filled with SiO 2 compared to without filler.…”
Section: Introductionmentioning
confidence: 99%